2014
DOI: 10.1530/jme-13-0302
|View full text |Cite
|
Sign up to set email alerts
|

Puerarin protects pancreatic β-cell survival via PI3K/Akt signaling pathway

Abstract: Pancreatic b-cell loss because of apoptosis is the major cause of type 1 diabetes (T1D) and late stage T2D. Puerarin possesses anti-diabetic properties; whether it acts directly on pancreatic b-cell is not clear. This study was designed to investigate the effects of puerarin on pancreatic b-cell survival and function. Diabetes was induced in male C57BL/6 mice by a single peritoneal injection of streptozotocin (STZ). Pancreatic b-cell survival and function were assessed in diabetic mice by measuring b-cell apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 29 publications
0
45
0
Order By: Relevance
“…A previous study demonstrated that puerarin protected pancreatic β-cell survival via the P13K/Akt signaling pathway (25). Neuroprotective effects of puerarin against beta-amyloid-induced neurotoxicity in PC12 cells were associated with activation of the PI3K-dependent signaling pathway (26).…”
Section: Discussionmentioning
confidence: 92%
“…A previous study demonstrated that puerarin protected pancreatic β-cell survival via the P13K/Akt signaling pathway (25). Neuroprotective effects of puerarin against beta-amyloid-induced neurotoxicity in PC12 cells were associated with activation of the PI3K-dependent signaling pathway (26).…”
Section: Discussionmentioning
confidence: 92%
“…A recent study indicated that puerarin restrained the progression of cardiac hypertrophy and apoptosis, which was probably mediated by the blockade of PI3K/Akt and JNK signaling pathways (23). In diabetic mice, puerarin exerted a protective effect on pancreatic β-cell function and survival, which was mediated via the PI3K/Akt pathway (24). Treatment with puerarin effectively inhibited lead-induced apoptosis in the kidney, which was associated with its antioxidant activity and its ability to modulate the PI3K/Akt/endothelial NO synthase signaling pathway (25).…”
Section: Discussionmentioning
confidence: 99%
“…In SCI model, activation of the PI3K/Akt has also been demonstrated to mediate recovery of motor function [46]. Numerous bioactivities of puerarin were mediated through regulating the PI3K/Akt signaling pathway, including protection of pancreatic β-cell [47], prevention of osteoporosis [48], attenuation of hepatic fibrosis [49], alleviation of cardiac hypertrophy [50], as well as neuroprotection [51][52][53]. Interestingly, the majority of studies demonstrated that puerarin exerted bioactivities via activating the PI3K/Akt pathway, whereas some of the studies reported that the therapeutic effects of puerarin were mediated via blocking PI3K/Akt [49,50].…”
Section: Discussionmentioning
confidence: 99%